An Algorithm for Parameters Estimation of Autoregressive Model of Basic Speech Units - I. V. Gubochkin (Моделирование и анализ информационных систем)
The article considers the problem of estimating autoregressive model parameters of elementary speech units such as phonemes. It is suggested an iterative algorithm based on the Newton numerical minimization technique to search an autoregressive model of phonemes specified its multiple samples. For this purpose the analytical expressions of the gradient and the Hessian of Kullback–Leibler information divergence between autoregressive models were computed. Experimental studies on a set of English phonemes showed that the developed algorithm requires less computational effort for large amounts of data, and iterations count depends little on the amount of input data as opposed to reference phoneme selection algorithm based on the criterion of a minimum sum of information divergence. Moreover, the proposed algorithm allows finding models of phonemes, which provide a higher probability of correct recognition.